Hygrothermal performance of cross-laminated timber wall assemblies: A stochastic approach. (15th February 2016) - Wang, Lin; Ge, Hua
Abstract: Cross-laminated timber (CLT) panels have the potential market in North America for building mid-rise or even taller structures due to their good structural and fire safety performance, carbon storage capacity, light weight, and prefabricated nature. However, prolonged exposure to moisture during construction and in service is a durability concern for most wood products including CLT. This paper presents the evaluation of the hygrothermal performance of CLT wall assemblies through simulations using a stochastic approach to account for the uncertainty of material properties, boundary conditions, and environmental loads. The moisture content of the CLT panel is used as the performance indicator. The influential factors are categorized into continuous and discrete random variables. The influence of the continuous random variables including material properties, boundary conditions and cladding ventilation rate is investigated under conditions represented by different combinations of the discrete random variables including wall configurations, orientation and rain leakage rate. The critical factors that lead to high moisture content are identified under each condition and the interaction between the discrete and continuous random variables is analyzed. The stochastic results show that the CLT wall assembly with low vapor permeance material placed outboard the CLT panel has a higher risk of moisture problem than CLT wall assembly with high vapor permeance material placed outboard the CLT panel. The sensitivity analysis indicates that the significance of the stochastic parameters on the hygrothermal performance of CLT panel depends on environmental loads, especially the rain load, and wall configurations. Highlights: Hygrothermal performance of CLT walls evaluated using a stochastic approach. The significance of influential parameters depends on wall configurations. The influence of material properties is more significant for CLT wall with low permeance WRB without rain leakage. The influence of boundary conditions is more significant for CLT wall with high permeance WRB. CLT wall with low permeance WRB has higher risk of moisture problem.